Campylobacter sp como perigo biológico na produção de peito de frango maturado - Butrico, Márcio Roberto [UNESP] (2014)
Campylobacter sp is the pathogen involved in most cases of foodborne diseases in the world. A major source is chicken meat due to poor preparation or cross-contamination during its handling. Nowadays, customers seek for chicken products with higher added value and some slaughterhouses have used aging procedures , which consists of keeping meat under low temperature for a certain period of time, untill natural enzymes confer more tenderness to it. The aim of this study was to identify whether Campylobacter sp is a biological hazard to be considered in the hazard analysis of aged chicken breast production. To do that, six flocks from different farms were tested for the presence of Campylobacter coli, Campylobacter jejuni and Campylobacter lari before slaughter (n=1500) using a commercial kit for Multiplex RT-PCR assay. Consecutively, samples from those flocks were taken at the evisceration before and after the Critical Control Point for visible ingesta contamination; before and after chilling; before and after aging (24 h) and after freezing, besides surface swabs of two equipments in contact with products. For each step thirty samples were gathered (n = 240) and six swabs per equipment (n = 12) to be analyzed by the Multiplex qRT-PCR method for the three Campylobacter serovars, including total coliforms and E. coli counts by Petrifilm plates. From the three serovars tested, Campylobacter jejuni and Campylobacter coli were recovered from the samples, but not Campylobacter lari. Although only one of the six flocks was pre-slaughter positive for Campylobacter jejuni, positive samples were recovered from all the other flocks, at least for one of the serovars tested in one of the steps. E.coli and total coliforms counts decreased significantly throughout process. The number of positive samples for one of the two species ...